2020
DOI: 10.1016/s1473-3099(20)30434-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary post-mortem findings in a series of COVID-19 cases from northern Italy: a two-centre descriptive study

Abstract: Background COVID-19 is characterised by respiratory symptoms, which deteriorate into respiratory failure in a substantial proportion of cases, requiring intensive care in up to a third of patients admitted to hospital. Analysis of the pathological features in the lung tissues of patients who have died with COVID-19 could help us to understand the disease pathogenesis and clinical outcomes.Methods We systematically analysed lung tissue samples from 38 patients who died from COVID-19 in two hospitals in northern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

106
1,270
6
54

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,239 publications
(1,436 citation statements)
references
References 20 publications
106
1,270
6
54
Order By: Relevance
“…Strikingly, however, some autopsy series reported no cases with intra-alveolar neutrophils (e.g., 0/80; Edler et al, 2020), even as others reported intra-alveolar neutrophils in 81.5% of their cases (31/38, excluding five cases with "abscesses"; Carsana, 2020). The latter finding is comparable to what Veras et al saw (60%) in their series (Veras et al, 2020 Preprint).…”
Section: Neutrophils or Not?mentioning
confidence: 51%
See 1 more Smart Citation
“…Strikingly, however, some autopsy series reported no cases with intra-alveolar neutrophils (e.g., 0/80; Edler et al, 2020), even as others reported intra-alveolar neutrophils in 81.5% of their cases (31/38, excluding five cases with "abscesses"; Carsana, 2020). The latter finding is comparable to what Veras et al saw (60%) in their series (Veras et al, 2020 Preprint).…”
Section: Neutrophils or Not?mentioning
confidence: 51%
“…Aside from the three cases noted by Barnes et al (2020), I found English-language reports of open autopsies of 277 people who succumbed to COVID-19 in Italy (Carsana, 2020), Germany (Edler et al, 2020), Switzerland, and the United States (Magro et al, 2020; five additional references will be provided on request). The following tabulation excludes cases where the terms "sepsis," "purulence," or "abscess" were mentioned.…”
Section: Neutrophils or Not?mentioning
confidence: 99%
“…COVID-19 primarily is a respiratory tract infection with signi cant systemic impaction on cardiovascular, neurologic, gastrointestinal, hematopoietic, hemostatic, and immune systems [17][18][19]. It is now widely accepted that a sort of disseminated intravascular coagulation (DIC) may develop with platelet consumption and hemorrhagic risk [19][20][21]. Recent studies show that the SARS-COV-2 provokes a diffuse damage to the vascular endothelium [20,21].…”
Section: Covid-19mentioning
confidence: 99%
“…It is now widely accepted that a sort of disseminated intravascular coagulation (DIC) may develop with platelet consumption and hemorrhagic risk [19][20][21]. Recent studies show that the SARS-COV-2 provokes a diffuse damage to the vascular endothelium [20,21]. In a large autoptic series [21], all cases presented more or less degree of endothelial damage and arteriolar thrombosis was evident in 87% of cases.…”
Section: Covid-19mentioning
confidence: 99%
“…One of the key clinical features of COVID19 is upregulation of the pro-thrombotic phenotype and microvascular complications, leading to COVID19-associated coagulopathy (7). This is characterized by venous, arterial, and microvascular thrombosis despite the use of anti-coagulant therapies (32)(33)(34)(35)(36)(37)(38). Our study provides compelling evidence of COVID19 associated changes in coagulation-related gene expression levels that may exacerbate thrombosis caused by endothelial cell injury and platelet activation in COVID19+ ICU patients (7).…”
Section: Discussionmentioning
confidence: 79%